1988
DOI: 10.1097/00006254-198807000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Inter-Observer Variability in the Assessment of Intrapartum Cardiotocograms

Abstract: The diagnostic value of a test depends on the variabilityof thetest resultsand theaccuracyofthe test. Theobject of this investigation was to estimate the observer variability and the accuracy, when intrapartum CTGs were assessed by experienced obstetricians. Fifty CTGs were evaluated twice by four obstetricians. They were asked to identify the CTGs belonging to the compromised infants. They were told the criteria for a compromised infant and the incidence (one-third).Eleven (22%) of the CTGs were assessed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 0 publications
2
50
0
5
Order By: Relevance
“…Respondents in that study called attention to the difficulty of CTG interpretation during labor and showed mixed satisfaction, with some midwives skeptical of its advantages. Another study similarly showed a demand for an alternative to CTG surveillance to counter the difficulty in its interpretation and strong intraand inter-operator variability [8].…”
Section: Discussionmentioning
confidence: 99%
“…Respondents in that study called attention to the difficulty of CTG interpretation during labor and showed mixed satisfaction, with some midwives skeptical of its advantages. Another study similarly showed a demand for an alternative to CTG surveillance to counter the difficulty in its interpretation and strong intraand inter-operator variability [8].…”
Section: Discussionmentioning
confidence: 99%
“…L'analyse et l'interprétation des anomalies du RCF restent (très) variables selon les observateurs, de même que pour le même observateur en fonction du temps ou a posteriori après connaissance de l'issue néonatale [19,20] (NP2).…”
Section: Classifications Des Anomalies Du Rcfunclassified
“…Néanmoins, cette méthode de surveillance reste largement répandue parce qu'elle présente certains avantages dont la traçabilité et la possibilité de structurer les indications des prélèvements au scalp foetal [3,4]. L'incapacité de l'ERCF pour prédire l'acidose foetale est pour une part en relation avec un défaut d'interprétation cohérente et systématique des tracés [5] : en effet, les mauvais scores de la concordance d'interprétation interet intra-observateurs laissent peser un sérieux doute sur la qualité de l'analyse telle qu'elle est assumée par différents intervenants dans les études observationnelles rétrospec-tives [6,7].…”
Section: Introductionunclassified